A role for Rtt109 in buffering gene-dosage imbalance during DNA replication. (3rd July 2016) - Voichek, Yoav; Bar-Ziv, Raz; Barkai, Naama
ABSTRACT: Chromatin can function as an integrator of DNA-related processes, allowing communication, for example, between DNA replication and gene transcription. Such communication is needed to overcome the gene-dosage imbalance introduced during DNA replication, when certain genes are replicated prior to others. Increased transcription of early replicating genes could alter regulatory balances. This does not occur, suggesting a mechanism that suppresses expression from newly replicated DNA. Critical to this buffering is Rtt109, which acetylates the internal K56 residue of newly synthesized histone H3 prior to incorporation onto DNA. H3K56ac distinguishes replicated from non-replicated DNA, communicating this information to the transcription machinery to ensure expression homeostasis during S phase.